(untitled) (African Journal of Public Administration & Management, 2026)
Information security is commonly described through key attributes that guide the protection of digital & physical information. CIA Triad model: Confidentiality so accessibility only to authorised individuals Integrity ensures accuracy, completeness and reliability of information Availability – authorised users can access information and systems when required.